2023
DOI: 10.1080/14686996.2023.2242262
|View full text |Cite
|
Sign up to set email alerts
|

A La 2 O 3 /MXene composite electrode for supercapacitors with improved capacitance and cycling performance

Abstract: Developing efficient electrode materials is a key towards high power electrochemical energy storage devices. Two-dimensional (2D) MXene shows excellent conductivity and electrochemical performance among other materials. However, the restacking of MXene layers may degrade their specific capacity and cycling performance. Considering this challenge, here we have designed a composite made of 2D MXene nanosheets and lanthanum oxide (La 2 O 3 ) nanoparticles to overcome … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 64 publications
1
1
0
Order By: Relevance
“…This behavior can be attributed to the presence of NiO sheets on the surface of Ti 3 C 2 -MXene, which contribute to this increased resistance. The Ti 3 C 2 -MXene/NiO/CsPbI 3 composites stood out in the Nyquist plot by displaying the smallest diameter among the samples [43]. This observation confirmed the lowest resistance and highest conductivity compared to the Ti 3 C 2 -MXene nanosheets and Ti 3 C 2 -MXene/NiO samples [44,45].…”
Section: Charge-transfer Behavior Of Ti3c2-mxene/nio/cspbi3 Compositessupporting
confidence: 54%
“…This behavior can be attributed to the presence of NiO sheets on the surface of Ti 3 C 2 -MXene, which contribute to this increased resistance. The Ti 3 C 2 -MXene/NiO/CsPbI 3 composites stood out in the Nyquist plot by displaying the smallest diameter among the samples [43]. This observation confirmed the lowest resistance and highest conductivity compared to the Ti 3 C 2 -MXene nanosheets and Ti 3 C 2 -MXene/NiO samples [44,45].…”
Section: Charge-transfer Behavior Of Ti3c2-mxene/nio/cspbi3 Compositessupporting
confidence: 54%
“…As a recent emerged two-dimensional (2D) transition-metal carbides and/or nitrides [42], MXene has been widely used in functional materials based on its unique structure [43] and excellent electrical properties [44]. Since Y. Gogotsi et al first reported the application of MXene in EMI shielding in 2016 [45], MXene has been widely noted for its low density and ease of processing compared to metal materials [46,47].…”
Section: Introductionmentioning
confidence: 99%